Educational Perspectives: Knitting Togetherness and Influencing the Mindset of Social Society - Rasyid, Ramli; Apriani, Leni; Muh. Febriansyah, Aji; Reski, Fridaytri; Saputra, Agung; Mufti Basri, Tifatul (Advances In Social Humanities Research, 2024)
This research discusses an educational perspective that focuses on togetherness and the influence of society's mindset. There is an increasingly rapid development of the times with all forms of global change that are increasingly widespread and felt in all aspects of life. This study reveals that Indonesia has many different cultures, including likes, races, customs, and certain religions. This requires something to be made into a guideline so that divisions do not occur due to these differences.